Desperate Times, Unprecedented Measures: The Confirmation of Gen. George C. Marshall to Serve as Secretary of Defense - Colin Adler (The Journal of Undergraduate Research, 2025)
Throughout the course of American history there are few men that have given more to their country than General George Catlett Marshall Jr. In his fifty-seven years as a public servant, Marshall served as an operations officer, the 13th Deputy Chief of Staff of the United States Army, 15th Chief of Staff of the United States Army, United States Special Envoy to China, 50th United States Secretary of State, 10th President of the American Red Cross, and 3rd United States Secretary of Defense. As Army Chief of Staff, Marshall orchestrated the largest expansion in U.S. military history, becoming a five-star general in the process and being named Time magazine’s Man of the Year in 1943. As Secretary of State, he was one of the main architects of the Marshall Plan which provided 12 billion in aid for the recovery of Western Europe in the aftermath of World War II, earning him the Time Man of the Year honor once again as well as a Nobel Peace Prize in 1953. By 1950 Marshall had established a reputation as both a military man and a statesman, making him an ideal replacement for Secretary of Defense Louis A. Johnson, whose failure to prepare for the Korean War led to his removal by Truman. Due to his status as a five-star general at the time of his nomination, Marshall’s appointment to the position of Secretary of Defense raised some concerns over the principle of civilian control of the military, but was largely approved of by the senate. Marshall’s appointment to Secretary of Defense in a time of war also highlights the rising concerns over national security in the United States, a more aggressive American military presence overseas, and the increased emphasis on defense spending in light of the looming Soviet threat in the Cold War.